5.1.24 Problems 2301 to 2400

Table 5.47: First order ode

#

ODE

Mathematica

Maple

5216

\[ {}\left (\cot \left (x \right )-2 y^{2}\right ) y^{\prime } = y^{3} \csc \left (x \right ) \sec \left (x \right ) \]

5217

\[ {}3 y^{\prime } y^{2} = 1+x +a y^{3} \]

5218

\[ {}\left (x^{2}-3 y^{2}\right ) y^{\prime }+1+2 x y = 0 \]

5219

\[ {}\left (2 x^{2}+3 y^{2}\right ) y^{\prime }+x \left (3 x +y\right ) = 0 \]

5220

\[ {}3 \left (x^{2}-y^{2}\right ) y^{\prime }+3 \,{\mathrm e}^{x}+6 x y \left (1+x \right )-2 y^{3} = 0 \]

5221

\[ {}\left (3 x^{2}+2 x y+4 y^{2}\right ) y^{\prime }+2 x^{2}+6 x y+y^{2} = 0 \]

5222

\[ {}\left (1-3 x +2 y\right )^{2} y^{\prime } = \left (4+2 x -3 y\right )^{2} \]

5223

\[ {}\left (1-3 x^{2} y+6 y^{2}\right ) y^{\prime }+x^{2}-3 x y^{2} = 0 \]

5224

\[ {}\left (x -6 y\right )^{2} y^{\prime }+a +2 x y-6 y^{2} = 0 \]

5225

\[ {}\left (x^{2}+y^{2} a \right ) y^{\prime } = x y \]

5226

\[ {}\left (x^{2}+x y+y^{2} a \right ) y^{\prime } = a \,x^{2}+x y+y^{2} \]

5227

\[ {}\left (a \,x^{2}+2 x y-y^{2} a \right ) y^{\prime }+x^{2}-2 a x y-y^{2} = 0 \]

5228

\[ {}\left (a \,x^{2}+2 b x y+c y^{2}\right ) y^{\prime }+k \,x^{2}+2 a x y+b y^{2} = 0 \]

5229

\[ {}x \left (1-y^{2}\right ) y^{\prime } = \left (x^{2}+1\right ) y \]

5230

\[ {}x \left (3 x -y^{2}\right ) y^{\prime }+\left (5 x -2 y^{2}\right ) y = 0 \]

5231

\[ {}x \left (x^{2}+y^{2}\right ) y^{\prime } = \left (x^{2}+x^{4}+y^{2}\right ) y \]

5232

\[ {}x \left (1-x^{2}+y^{2}\right ) y^{\prime }+\left (-y^{2}+x^{2}+1\right ) y = 0 \]

5233

\[ {}x \left (a -x^{2}-y^{2}\right ) y^{\prime }+\left (a +x^{2}+y^{2}\right ) y = 0 \]

5234

\[ {}x \left (2 x^{2}+y^{2}\right ) y^{\prime } = \left (2 x^{2}+3 y^{2}\right ) y \]

5235

\[ {}\left (x \left (a -x^{2}-y^{2}\right )+y\right ) y^{\prime }+x -\left (a -x^{2}-y^{2}\right ) y = 0 \]

5236

\[ {}x \left (a +y\right )^{2} y^{\prime } = b y^{2} \]

5237

\[ {}x \left (x^{2}-x y+y^{2}\right ) y^{\prime }+\left (y^{2}+x y+x^{2}\right ) y = 0 \]

5238

\[ {}x \left (x^{2}-x y-y^{2}\right ) y^{\prime } = \left (x^{2}+x y-y^{2}\right ) y \]

5239

\[ {}x \left (x^{2}+a x y+y^{2}\right ) y^{\prime } = \left (x^{2}+b x y+y^{2}\right ) y \]

5240

\[ {}x \left (x^{2}-2 y^{2}\right ) y^{\prime } = \left (2 x^{2}-y^{2}\right ) y \]

5241

\[ {}x \left (2 y^{2}+x^{2}\right ) y^{\prime } = \left (2 x^{2}+3 y^{2}\right ) y \]

5242

\[ {}2 x \left (5 x^{2}+y^{2}\right ) y^{\prime } = x^{2} y-y^{3} \]

5243

\[ {}x \left (x^{2}+a x y+2 y^{2}\right ) y^{\prime } = \left (a x +2 y\right ) y^{2} \]

5244

\[ {}3 y^{2} y^{\prime } x = 2 x -y^{3} \]

5245

\[ {}\left (1-4 x +3 x y^{2}\right ) y^{\prime } = \left (2-y^{2}\right ) y \]

5246

\[ {}x \left (x -3 y^{2}\right ) y^{\prime }+\left (2 x -y^{2}\right ) y = 0 \]

5247

\[ {}3 x \left (y^{2}+x \right ) y^{\prime }+x^{3}-3 x y-2 y^{3} = 0 \]

5248

\[ {}x \left (x^{3}-3 x^{3} y+4 y^{2}\right ) y^{\prime } = 6 y^{3} \]

5249

\[ {}6 y^{2} y^{\prime } x +x +2 y^{3} = 0 \]

5250

\[ {}x \left (x +6 y^{2}\right ) y^{\prime }+x y-3 y^{3} = 0 \]

5251

\[ {}x \left (x^{2}-6 y^{2}\right ) y^{\prime } = 4 \left (x^{2}+3 y^{2}\right ) y \]

5252

\[ {}x \left (3 x -7 y^{2}\right ) y^{\prime }+\left (5 x -3 y^{2}\right ) y = 0 \]

5253

\[ {}y^{2} y^{\prime } x^{2}+1-x +x^{3} = 0 \]

5254

\[ {}\left (1-x^{2} y^{2}\right ) y^{\prime } = x y^{3} \]

5255

\[ {}\left (1-x^{2} y^{2}\right ) y^{\prime } = \left (x y+1\right ) y^{2} \]

5256

\[ {}x \left (x y^{2}+1\right ) y^{\prime }+y = 0 \]

5257

\[ {}x \left (x y^{2}+1\right ) y^{\prime } = \left (2-3 x y^{2}\right ) y \]

5258

\[ {}x^{2} \left (a +y\right )^{2} y^{\prime } = \left (x^{2}+1\right ) \left (y^{2}+a^{2}\right ) \]

5259

\[ {}\left (x^{2}+1\right ) \left (1+y^{2}\right ) y^{\prime }+2 x y \left (1-y^{2}\right ) = 0 \]

5260

\[ {}\left (x^{2}+1\right ) \left (1+y^{2}\right ) y^{\prime }+2 x y \left (1-y\right )^{2} = 0 \]

5261

\[ {}\left (1-x^{3}+6 x^{2} y^{2}\right ) y^{\prime } = \left (6+3 x y-4 y^{3}\right ) x \]

5262

\[ {}x \left (3+5 x -12 x y^{2}+4 x^{2} y\right ) y^{\prime }+\left (3+10 x -8 x y^{2}+6 x^{2} y\right ) y = 0 \]

5263

\[ {}x^{3} \left (1+y^{2}\right ) y^{\prime }+3 x^{2} y = 0 \]

5264

\[ {}x \left (1-x y\right )^{2} y^{\prime }+\left (1+x^{2} y^{2}\right ) y = 0 \]

5265

\[ {}\left (1-y^{2} x^{4}\right ) y^{\prime } = x^{3} y^{3} \]

5266

\[ {}\left (3 x -y^{3}\right ) y^{\prime } = x^{2}-3 y \]

5267

\[ {}\left (x^{3}-y^{3}\right ) y^{\prime }+x^{2} y = 0 \]

5268

\[ {}\left (y^{3}+x^{3}\right ) y^{\prime }+x^{2} \left (a x +3 y\right ) = 0 \]

5269

\[ {}\left (x -x^{2} y-y^{3}\right ) y^{\prime } = x^{3}-y+x y^{2} \]

5270

\[ {}\left (x \,a^{2}+y \left (x^{2}-y^{2}\right )\right ) y^{\prime }+x \left (x^{2}-y^{2}\right ) = a^{2} y \]

5271

\[ {}\left (a +x^{2}+y^{2}\right ) y y^{\prime } = x \left (a -x^{2}-y^{2}\right ) \]

5272

\[ {}\left (3 x^{2}+y^{2}\right ) y y^{\prime }+x \left (x^{2}+3 y^{2}\right ) = 0 \]

5273

\[ {}\left (a -3 x^{2}-y^{2}\right ) y y^{\prime }+x \left (a -x^{2}+y^{2}\right ) = 0 \]

5274

\[ {}2 y^{3} y^{\prime } = x^{3}-x y^{2} \]

5275

\[ {}y \left (2 y^{2}+1\right ) y^{\prime } = x \left (2 x^{2}+1\right ) \]

5276

\[ {}\left (3 x^{2}+2 y^{2}\right ) y y^{\prime }+x^{3} = 0 \]

5277

\[ {}\left (5 x^{2}+2 y^{2}\right ) y y^{\prime }+x \left (x^{2}+5 y^{2}\right ) = 0 \]

5278

\[ {}\left (x^{2}-x^{3}+3 x y^{2}+2 y^{3}\right ) y^{\prime }+2 x^{3}+3 x^{2} y+y^{2}-y^{3} = 0 \]

5279

\[ {}\left (3 x^{3}+6 x^{2} y-3 x y^{2}+20 y^{3}\right ) y^{\prime }+4 x^{3}+9 x^{2} y+6 x y^{2}-y^{3} = 0 \]

5280

\[ {}\left (x^{3}+a y^{3}\right ) y^{\prime } = x^{2} y \]

5281

\[ {}x y^{3} y^{\prime } = \left (-x^{2}+1\right ) \left (1+y^{2}\right ) \]

5282

\[ {}x \left (x -y^{3}\right ) y^{\prime } = \left (3 x +y^{3}\right ) y \]

5283

\[ {}x \left (y^{3}+2 x^{3}\right ) y^{\prime } = \left (2 x^{3}-x^{2} y+y^{3}\right ) y \]

5284

\[ {}x \left (-y^{3}+2 x^{3}\right ) y^{\prime } = \left (-2 y^{3}+x^{3}\right ) y \]

5285

\[ {}x \left (x^{3}+3 x^{2} y+y^{3}\right ) y^{\prime } = \left (3 x^{2}+y^{2}\right ) y^{2} \]

5286

\[ {}x \left (-2 y^{3}+x^{3}\right ) y^{\prime } = \left (-y^{3}+2 x^{3}\right ) y \]

5287

\[ {}x \left (x^{4}-2 y^{3}\right ) y^{\prime }+\left (2 x^{4}+y^{3}\right ) y = 0 \]

5288

\[ {}x \left (x +y+2 y^{3}\right ) y^{\prime } = y \left (x -y\right ) \]

5289

\[ {}\left (5 x -y-7 x y^{3}\right ) y^{\prime }+5 y-y^{4} = 0 \]

5290

\[ {}x \left (1-2 x y^{3}\right ) y^{\prime }+\left (1-2 x^{3} y\right ) y = 0 \]

5291

\[ {}x \left (2-x y^{2}-2 x y^{3}\right ) y^{\prime }+1+2 y = 0 \]

5292

\[ {}\left (2-10 x^{2} y^{3}+3 y^{2}\right ) y^{\prime } = x \left (1+5 y^{4}\right ) \]

5293

\[ {}x \left (a +b x y^{3}\right ) y^{\prime }+\left (a +c \,x^{3} y\right ) y = 0 \]

5294

\[ {}x \left (1-2 x^{2} y^{3}\right ) y^{\prime }+\left (1-2 y^{2} x^{3}\right ) y = 0 \]

5295

\[ {}x \left (1-x y\right ) \left (1-x^{2} y^{2}\right ) y^{\prime }+\left (x y+1\right ) \left (1+x^{2} y^{2}\right ) y = 0 \]

5296

\[ {}\left (x^{2}-y^{4}\right ) y^{\prime } = x y \]

5297

\[ {}\left (x^{3}-y^{4}\right ) y^{\prime } = 3 x^{2} y \]

5298

\[ {}\left (a^{2} x^{2}+\left (x^{2}+y^{2}\right )^{2}\right ) y^{\prime } = a^{2} y x \]

5299

\[ {}2 \left (x -y^{4}\right ) y^{\prime } = y \]

5300

\[ {}\left (4 x -x y^{3}-2 y^{4}\right ) y^{\prime } = \left (2+y^{3}\right ) y \]

5301

\[ {}\left (a \,x^{3}+\left (a x +b y\right )^{3}\right ) y y^{\prime }+x \left (\left (a x +b y\right )^{3}+b y^{3}\right ) = 0 \]

5302

\[ {}\left (x +2 y+2 x^{2} y^{3}+y^{4} x \right ) y^{\prime }+\left (y^{4}+1\right ) y = 0 \]

5303

\[ {}2 x \left (x^{3}+y^{4}\right ) y^{\prime } = \left (x^{3}+2 y^{4}\right ) y \]

5304

\[ {}x \left (1-x^{2} y^{4}\right ) y^{\prime }+y = 0 \]

5305

\[ {}\left (x^{2}-y^{5}\right ) y^{\prime } = 2 x y \]

5306

\[ {}x \left (x^{3}+y^{5}\right ) y^{\prime } = \left (x^{3}-y^{5}\right ) y \]

5307

\[ {}x^{3} \left (1+5 x^{3} y^{7}\right ) y^{\prime }+\left (3 x^{5} y^{5}-1\right ) y^{3} = 0 \]

5308

\[ {}\left (1+a \left (x +y\right )\right )^{n} y^{\prime }+a \left (x +y\right )^{n} = 0 \]

5309

\[ {}x \left (a +x y^{n}\right ) y^{\prime }+b y = 0 \]

5310

\[ {}f \left (x \right ) y^{m} y^{\prime }+g \left (x \right ) y^{m +1}+h \left (x \right ) y^{n} = 0 \]

5311

\[ {}y^{\prime } \sqrt {b^{2}+y^{2}} = \sqrt {a^{2}+x^{2}} \]

5312

\[ {}y^{\prime } \sqrt {b^{2}-y^{2}} = \sqrt {a^{2}-x^{2}} \]

5313

\[ {}y^{\prime } \sqrt {y} = \sqrt {x} \]

5314

\[ {}\left (1+\sqrt {x +y}\right ) y^{\prime }+1 = 0 \]

5315

\[ {}y^{\prime } \sqrt {x y}+x -y = \sqrt {x y} \]